Senator Ayogu Eze v. Hon. Ifeanyi Lawrence Ugwuanyi and Ors: An Answer to Locus Standi and Jurisdiction in Nigerian Jurisprudence - Godwin Emeka Ngwu (Law and Economy, 2023)
Equally settled is the fact that as at the moment, the only window opened for the courts to entertain action on and/or concerning nomination of candidates for any election by political parties is as provided under section 87(8) or (9) or (10) of the Electoral, Act 2010, (as amended)... “As a result of the above provision conferring (sic) this court has held, in very many cases, that only an aspirant in the primary election conducted by the political party can question the result or nomination or declaration of any person by the party as the winner of the primary election. Consequently, the sponsored candidate of the political party concerned in the election in issue. It follows, therefore, that no other person or member of the political party concerned, has the locus to challenge or question the nomination of any candidate by a political party for any election.” Even at the risk of repetition, the appellant was not a candidate in the governorship primary election that was held in Enugu State in 2015, as such he lacked the locus to challenge the declaration of the 4th respondent as the winner of the said primary. However, section 87(9) of the Electoral Act, 2010 (as amended) gives the courts very limited jurisdiction to ensure that in the selection or nomination process, political parties do not act arbitrarily but within the confines of their constitution and Electoral Guidelines, and in accordance with the provisions of the Electoral Act. The appellant failed to bring himself within the purview of section 87 (9) of the Electoral Act He was not an aspirant in the primary election from which the 4th respondent emerged. He therefore lacked the locus standi to institute the action. There is no reason to interfere with the sound reasoning of the court. Jurisdiction is the bedrock of every litigation be it civil of criminal, however, in this case, the court is heavily clothed with jurisdiction to entertain a matter bordering on political parties primary elections by virtue of section 87(8) or (9) or (10) of the Electoral Act 2010, as amended..., Locus-Standi is an indisputable principle of law that can be raised at any stage of judicial proceedings, locus-Standi determines whether a party to a litigation is armed with power or legal capacity to institute an action before the courts of law, however Senator Ayogu Eze who is the plaintiff/ respondent lacked the right of action, on his failure to participate in primary elections organized by the national committee headed by king Asara; has forfeited or negatived his legal capacity to institute action in the court of first instance.